The Influence of the Financial Distress, Conflict of Interest, and Litigation Risk on Accounting Conservatism - Mar’atus Sholikhah , Ristya; Wilujeng Suryani, Ani (KnE Social Sciences, 2020)
This study aims to determine the effect of financial distress, conflict of interest, and litigation risk on the implementation of accounting conservatism. Data were collected from 20 annual reports of a manufacturing company in Indonesia, which is being experienced financial distress from the period 2014 to 2017. Model data analysis in this research is panel data regression. The results of this study indicate that financial distress can reduce the application of accounting conservatism. Relatively low conflicts of interest between investors and creditors have not been able to influence accounting conservatism. However, conservative reporting can avoid the litigation risk in the future. This research can be an input for companies to recognize early financial conditions, so they can overcome problems that might occur. For investors, creditors, and the government must monitor the behavior and actions of managers in presenting financial statements so as not to harm other parties. For further research can use financial that are prone to detect financial distress and add samples from other company sectors. Keywords: Accounting Conservatism, Financial Distress, Conflict of Interest, Litigation Risk